Penerapan Model Pembelajaran Picture And Picture Materi Sejarah Kelas VIII SMP Terpadu Abul Faidl Blitar - Moh Ihsan Soval Mubarok; Jani Jani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The background of this research is that the learning process is still carried out by the teacher, and students tend to be passive. Less conducive learning conditions such as daydreaming students, students are still less active in the learning process. Therefore, the picture and picture learning model is used in achieving optimal learning goals. The aims of this study were (1) to find out the inhibiting and supporting factors, and the impact of applying the picture and picture learning model on history material for Grade VIII students of SMP Terpadu Abul Faidl Wonodadi Blitar. This research uses descriptive qualitative research. Methods of data collection using observation, interviews and interviews to be analyzed inductively. Research result; (1) The steps of the picture and picture learning model in this study are conveying the competencies achieved, presenting the material as an introduction, the researcher reveals pictures of activities related to the material. The researcher selects students to take turns arranging the pictures into a logical sequence. The researcher asked the reason for the sequencing of the images. researchers build concepts according to the competencies achieved, conclusions, and closing. (2) Supporting factors only require pictures and adhesives. inhibiting factor difficult to find the appropriate image quality. (3) The positive impact of training students' reasoning and memory so as to improve student learning outcomes. negative impacts include, it takes a long time to prepare images, increases expenses, it is difficult to find suitable and good images.